Quaternary Element Incorporation Effects on Thermal Properties and Crystal-Micro Structure of Cu-Al-Fe High Temperature Shape Memory Alloys - Balci, Esra; Akpinar, Sinan (Int Center Applied Thermodynamics, 2021)
Recently, researchers have shown an increased interest in Cu based shape memory alloys due to their special characteristics, which can be used in high-temperature applications. In this study, ternary shape memory alloys in the form of CuAlFe with different ratios of iron and quaternary CuAlFe alloys containing Ni, Mn, and Ti were produced by arc melting. Then the produced alloys were kept at 900 degrees C for 24 hours to make sure that all constituents in the alloys were homogeneously distributed. The change in the transformation temperatures for all samples was checked out by Differential Scanning Calorimetry (DSC). Also, the change in the crystal structure and microstructure were determined by x-ray diffractometer (XRD) and scanning electron microscopy (SEM), respectively. The aim of this study is to compare the thermal and microstructural properties of quaternary alloys formed by adding Ni, Mn, and Ti elements to CuAlFe-based shape memory alloy with different rates, which is not available in the literature. The result of this study; although the electron concentration value increased, a significant decrease was observed in the values of the transformation temperatures. Increasing Fe-element decreased the transformation temperature non-linearly. Ni and Mn contents added to CuAlFe shape memory alloys have reduced transformation temperatures, such as A(f) and M-f. The XRD and SEM-EDX measurements showed the martensite phase with some produced compound precipitated in the matrix phase.
Keywords: CuAlFe; Shape memory alloys; crystal structure; transformation temperature; activation energy